Collective Actions and Challenges Analysis on Management of the Mekong River as Common Pool Resources - Ni Nyoman Clara Listya Dewi (Institute of International Studies, 2021)
The countries of the Indochinese peninsula think that the Mekong River is a shared resource that must be managed through cooperation between countries. However, because many countries exploit the resources in the Mekong River, it triggers an increase in environmental degradation. This phenomenon has prompted the establishment of the 1995 Mekong Agreement and the Mekong River Commission (MRC) which aims to agree on cooperation in sustainable development, conservation, and management of resources in river areas. However, as an upstream country, China did not want to join the Mekong River Commission. In fact, China initiated a new collaboration called the Lancang Mekong Cooperation Mechanism (LMCM) in 2016. In the concrete, China has implemented a mega dam construction project which is considered to be a contributor to environmental degradation. By utilizing Garret Hardin's (1968) views on the tragedy of the commons, this paper analyses the challenges, collective actions and efforts of countries in the Mekong River region in overcoming river management and the sources of the tragedy of the commons. Through several characteristics in the management of shared resources by Ostrom (1990) this paper finds that arrangements for shared resources are important to be systematically arranged by the government to prevent the tragedy of the commons. Institutions at the local level are very important to be able to develop appropriate institutional structures that are adapted to the social and economic life of the people along the Mekong River.